A Contextual and Collaborative Model for Improving Madrasah Diniyah Teacher Competence: A Case Study at MDT An Najah Pasongsongan Sumenep in 2026 - Kamilul Himam; Moh. Hamzah (Community: Jurnal Hasil Penelitian dan Pengabdian Masyarakat, 2026)
Improving teacher competency is a key factor in improving the quality of learning at Madrasah Diniyah Takmiliyah (MDT). Various studies indicate that the main weaknesses of MDT teachers lie in the pedagogical aspect, especially in planning, methods, and evaluation of learning. This study aims to analyze the condition of teacher competency, formulate a competency improvement model, and assess the effectiveness of its implementation at MDT An Najah Pasongsongan Sumenep. This study used a qualitative approach with a case study design. Data were collected through in-depth interviews, participant observation, and documentation, then analyzed using the Miles and Huberman interactive model. Data validity was maintained through triangulation and member checking. The results showed that teacher competency is heterogeneous. Professional and personality competencies are relatively good, while pedagogical competency still requires strengthening. The competency improvement model developed is contextual, collaborative, and sustainable through internal coaching, academic supervision, collective discussions, and teaching practice mentoring. The program implementation has had a positive impact on improving the quality of learning and teacher professional awareness, although not evenly distributed. This study confirms that a program based on local madrasah needs is an effective strategy in developing MDT teacher competency.